Co jest stawką w zakładzie Pascala? - Wiertlewska, Małgorzata (Poznańskie Studia Teologiczne, 2010)
The author draws on several literary and philosophical approaches to bring out some of the themes embedded in Pascal’s wager, such as: the world as an arena of one’s confrontation with one’s vision of oneself; the notions of ‘here’ and ‘there’ in relation to the intuition of the immortality of the individual human soul; God as an answer to human longing for a Witness; belief in God as ultimate concern for human life; the transnatural destiny of the human person. These existential insights are complemented by the analytical considerations and criticism of Pascal’s wager put forward by Richard Swinbume in his book Faith and Reason (2005). Swinburne’s inquiry pivots around the problem of a person’s responsibility for the beliefs he/she holds and what it means to be rational. The purpose of the article is to actualize the question: What is the stake in Pascal’s wager?